Answer :

Given sin-1 (sin (-600°))


= sin-1 (sin (-600 + 360 × 2))


We know that sin (2nπ + θ) = sin θ


= sin (sin 120°)


We know that sin-1 (sin θ) = π – θ, if θ [π/2, 3π/2]


= 180° - 120°


= 60°


sin-1 (sin (-600°)) = 60°


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers